2016
DOI: 10.1177/0047287515627029
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Associative Slogans on Tourists’ Attitudes and Travel Intention

Abstract: The study tests a model that examines the influence of characteristics of associative slogans on tourists’ attitudes toward slogan, attitudes toward destination, and travel intentions as well as the moderating effects of the need for cognition and destination familiarity on these relationships. Findings reveal that extremity has negative effects on attitudes toward slogan, attitudes toward destination, and travel intention; specificity has a positive effect on attitudes toward slogan; and relevancy has positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 60 publications
1
23
0
7
Order By: Relevance
“…Third, the eight-item flourishing scale proposed by Diener et al (2010) was used to measure different aspects of subjective well-being, including feelings of competence, positive relationship, and meaningful life. Fourth, the three-item scale of travel intention was used to measure satellite fans' future intentions to visit the home ground of the EPFL team (Zhang et al, 2017). All survey items were modified as necessary to suit the context of this study and were measured by the 7point Likert scale, ranging from (1) strongly disagree to (7) strongly agree.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Third, the eight-item flourishing scale proposed by Diener et al (2010) was used to measure different aspects of subjective well-being, including feelings of competence, positive relationship, and meaningful life. Fourth, the three-item scale of travel intention was used to measure satellite fans' future intentions to visit the home ground of the EPFL team (Zhang et al, 2017). All survey items were modified as necessary to suit the context of this study and were measured by the 7point Likert scale, ranging from (1) strongly disagree to (7) strongly agree.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Hence, this research supports and extends the findings of Chi and Qu (2008) suggesting a positive relationship between destination familiarity, image, satisfaction and loyalty. Zhang et al (2017) also found a complicated relationship between the characteristics of a destination’s slogan and a visitor’s destination familiarity, attitudes and intentions to visit. This is important as it suggest that information exposure, as well as primary (own) and secondary (others) experiences, form a person’s familiarity that then influences a person’s cognitive and affective images and ultimately determines their loyalty to a destination.…”
Section: Discussionmentioning
confidence: 99%
“…Tourists are likely to place greater weight on emotional images as they need to form a closer connection when evaluating and selecting a destination because they have greater direct and opportunity costs associated with visiting than a resident. Indeed, tourists are more likely to minimise or avoid risks associated with their travel decision-making forcing them to be more careful and dependent on their image and more likely to visit an established, rather than emerging destination (Sharifpour et al, 2014; Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pengembangan produk wisata penting dilakukan agar wisatawan tidak merasa jenuh saat berkunjung. Pengelola wisata Pantai Kenjeran juga harus menjaga citra baik wisatanya karena citra dari produk wisata yang terkait dengan destinasi wisata dan fasilitas pariwisata, secara langsung dapat memenuhi kebutuhan wisatawan (Zhang et al, 2017). Dahulu kawasan Pantai Kenjeran merupakan kawasan pantai yang kumuh dan tidak layak dijadikan sebagai obyek wisata karena selain kumuh, kawasan Pantai Kenjeran juga menjadi tempat yang rawan terjadi tindak kriminalitas (nativeindonesia.com, 2019).…”
Section: Pendahuluanunclassified
“…Multi dimensinya citra destinasi disebabkan oleh atribut yang disertakan cukup beragam dan saling terkait (Utama, 2017:222). Citra destinasi wisata didefinisikan sebagai citra dari produk wisata yang terkait dengan destinasi wisata dan fasilitas pariwisata, yang secara langsung dapat memenuhi kebutuhan wisatawan (Zhang et al, 2017). Menurut teori dari Utama (2017:219) dalam dunia pariwisata, citra dapat menggerakkan dan mendorong wisatawan untuk menentukan pilihan destinasi wisatanya.…”
Section: Citra Destinasiunclassified